The Legal Profile of Russian Eurobonds : Engineered against Speed - Farah Yacoub, Juan P. (World Bank, Washington, DC, 2022)
This paper provides an overview of the Russian Federation’s default history, the legal characteristics of the bonds, and potential issues for litigation should a default materialize. The paper’s main argument is that although it is not impenetrable, this Eurobond stock is more protective of the debtor than that of the usual emerging market country. It achieves this through preservation of all the defenses available under current law and the presence of broad language in key provisions. For instance, clauses providing for payment in a different currency if “reasons beyond its control” stop the debtor from paying in the denomination currency have drawn attention. The paper analyzes this and other characteristics, providing initial assessments on how the issues could play out. While the bonds’ characteristics could slow progress toward obtaining judgments when compared to other sovereign debts, they do not prevent them. Collecting on the judgments would be, as usual, the harder part. Ultimately, litigation over these debts could last a long time; other creditor versus foreign sovereign episodes involving less debtor-friendly instruments have lasted 15 years, and resolution and recovery would be highly contingent on political factors. Finally, the paper provides non-lawyers a general roadmap of debt litigation against foreign sovereigns in the United States and the United Kingdom.